Anxiety and depression and the related factors in nurses of Guilan University of Medical Sciences hospitals during COVID-19: A web-based cross-sectional study. (2020) - Pouralizadeh, Moluk; Bostani, Zahra; Maroufizadeh, Saman; Ghanbari, Atefeh; Khoshbakht, Maryam; Alavi, Seyed Amirhossein; Ashrafi, Sadra
Abstract: Background: The outbreak of COVID-19 is an unprecedented challenge to the health systems in Iran. We aimed to assess the psychological impact of this outbreak on nurses in the hospitals of Guilan University of Medical Sciences that is one of the top provinces of incidence of COVID-19. Methods: In a web-based cross-sectional study, 441 nurses working were selected from the hospitals, from 7 to 12 April 2020. Anxiety and depression were measured using the Generalized Anxiety Disorder-7 and the Patient Health Questionnaire-9, respectively. Simple and multiple logistic regression models were used to identify the factors related to anxiety and depression. Results: The majority were in contact with suspected or confirmed COVID-19 cases (93.4%) and their relatives had been infected with COVID-19 (42%). The mean of anxiety-7 and depression total scores were 8.64 ± 5.60 and 8.48 ± 6.19, respectively. Female (OR = 3.27, 95% CI = 1.01–10.64), working in COVID-19 designated hospital (OR = 1.82, 95% CI = 1.13–2.93), being suspected with COVID-19 infection (OR = 2.01, 95% CI = 1.25–3.26), and insufficient personal protective equipment (OR = 2.61, 95% CI = 1.68–4.06) were associated with anxiety. Depression was significantly associated with female sex (OR = 4.62, %95 CI = 1.24–17.16), having chronic disease (OR = 2.12, 95% CI = 1.20–3.74), being suspected or confirmed with COVID-19 infection (OR = 3.44, 95% CI = 2.11–5.59, and OR = 2.21, 95% CI = 1.04–4.70, respectively), and insufficient personal protective equipment (OR = 1.86, 95% CI = 1.19–2.91). Conclusion: The finding declares healthcare workers are at high risk for mental illness. Continuous supervision of the psychological consequences following infectious diseases outbreaks should be a part of the preparedness efforts of health care systems.